Surgical vs. Conservative Management for Lobar Intracerebral Hemorrhage, a Meta-Analysis of Randomized Controlled Trials - Akram, Muhammad Junaid; Zhao, Rui; Shen, Xue; Yang, Wen-Song; Deng, Lan; Li, Zuo-Qiao; Hu, Xiao; Zhao, Li-Bo; Xie, Peng; Li, Qi (Frontiers in Neurology, 2022)
Background Outcomes regarding the conventional surgical and conservative treatment for the lobar intracerebral hemorrhage (ICH) have not been previously compared. The current meta-analysis was designed to review and compile the evidence regarding the management of patients with lobar intracerebral hemorrhage. Methods Online electronic databases, including PubMed, Embase, Medline, Cochrane Library, and Google Scholar, were searched for randomized controlled trials (RCTs). Studies were selected on the basis of the inclusion and exclusion criteria. Trials with CT-confirmed lobar intracerebral hemorrhage patients of which treatment regimen was started within 72 h following the stroke were included. Low quality trials were excluded. Death or dependence was defined as primary outcome and death at the end of the follow up was the secondary outcome. Results One hundred five RCTs were screened and 96 articles were excluded on the basis of abstract. Nine articles were assessed for the eligibility and 7 trials were included that involved 1,102 patients. The Odds ratio (OR) for the primary outcome was 0.80 (95% CI, 0.62–1.04, p = 0.09) and for the secondary outcome was 0.79 (95%CI, 0.60–1.03, p = 0.09). Conclusion Our findings suggested that surgical treatments did not significantly improve the functional outcome as compared with the conservative medical management for patients with lobar ICH.